Nonparametric test in semiparametric analysis of covariance model for a crossover design with carryover effects - Almero, Leonard Allan F.
Abstract (A semiparametric mixed analysis of covariance model for a crossover design with carryoever effects is postulate. A hybrid of restricted maximum likelihood estimation and smoothing splines regression are imbedded into the backfitting algorithm is used to estimate the model. The responses are adjusted for covariate effect through a nonparametric function of the covariates. Simulations study indicates that a bootstrap-based test for variance components is correctly-sized for variance components. The test is powerful in testing for variance component and relatively robust to the magnitude of variance in the alternative hypothesis. Furthermore, the test is advantageous over ordinary analysis of covariance in the presence of misclassification error and in non-normal error on unbalanced data).
June 2018.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Analysis of covariance; Crossover design; Bootstrap-based hypothesis testing